Factors influencing employee’s turnover intention in banking sector in Penang / Arvindraj and Jaya Kumar Shanmugam - Nagarajah, Arvindraj Naidu; Shanmugam, Jaya Kumar (2019)
This study aims to investigate factors that influence employee’s turnover intention in banking sector in Penang. The are several factors expected to influence the employee’s turnover intention which are distributive justice, job stress, job satisfaction and compensation. A total of 150 bank employees from different banking sectors were selected and questionnaires were distributed to them. The collected data was analyzed using SPSS version 25. The results revealed that there is a significant relationship between all factors and employee’s turnover intention. All factors have an influence towards employee’s turnover intention. This study will help the bank management to identify the potential factors that influence their staff to quit from the current job. Several recommendations and suggestions for further research are also discussed at the end of this study.